LGG-37. ASSESSMENT OF EARLY STAGE AUTOPHAGY INHIBITION IN BRAFV600E BRAIN TUMOR CELL RESPONSE TO CHEMOTHERAPY. Issue 2 (22nd June 2018) - Zahedi, Shadi; Fitzwalter, Brent E; Gustafson, Daniel L; Morin, Andrew; Desmarais, Michele; Hoffman, Lindsey M; Levy, Jean M Mulcahy
Abstract: We have previously shown CNS tumors with the BRAF V600E mutation are autophagy dependent and late stage autophagy inhibition improves responses to targeted BRAF inhibitors (BRAFi) in sensitive and BRAFi resistant cells. Autophagy is a multi-stage process. Progress within the field has led to the development of agents targeting both early (initiation) and late (fusion) stages. Defining the most effective means of autophagy inhibition will be vital to future clinical trials. We evaluated early stage inhibition as a potential therapy for autophagy dependent CNS tumors. BRAFi-sensitive and BRAFi-resistant AM38 and 794 cell lines were evaluated for response to pharmacologic and genetic inhibition of ULK1 and VPS34, two crucial subunits of autophagy initiation complexes, in the presence or absence of a BRAFi, Vemurafenib. Pharmacologic inhibition of these targets reduced cell survival in a dose dependent manner, irrespective of RAFi sensitivity, as monitored by short-term and long-term growth assays. shRNA knockdown of ULK1 or VPS34 confirmed this autophagy specific effect. The combination of early stage inhibition and BRAFi was synergistic and led to higher cell death following treatments. Extent of autophagy inhibition was assessed by western blot and flow cytometry. Cells exhibited reduced autophagic flux upon treatment with pharmacologic and genetic early stage autophagy inhibition confirming the effects are related to autophagy. Inhibition of ULK1 and VPS34 are potentially viable clinical targets in autophagy dependent CNS tumors. Further evaluation is needed to determine if early stage autophagy inhibition is as potent as late stage inhibition to determine the optimal clinical target for patients.